Theoretical Underpinnings of Learner Engagement in Software Visualization System: A Systematic Literature Review Protocol - Abdullah Al-Sakkaf, Abdullah; Omar, Mazni; Ahmad, Mazida (International Journal of Engineering and Technology, 2018)
Having a solid theoretical foundation is essential for designing an effective software visualization (SV) tool. Despite the decades of developing different SV tools, there are still doubts about their effectiveness. Furthermore, learner engagement plays an important role in building a successful SV tool. In programming education, the problem of the high failure rates among students is still unresolved. Therefore, there is a need to understand the theories behind the exciting SV tools from the engagement perspective in order to have a road map for future tool construction. Yet the factors influencing learner engagement in SV tools are still unclear. This study set out to determine how to develop an SV design model to enhance student engagement in an introductory programming course. A systematic literature review (SLR) was used to obtain an overview of the current theoretical foundation used. The search identified a total of 432 papers between 2011 and 2017. This study examined 58 papers selected based on a well-defined selection process. In this paper, the contribution in constructing the protocol for SLR is presented as well as the preliminary results of the study. The researchers were in the process of data extraction phase to address the research questions. The expected outcomes of this review became the identification of a theoretical background used to construct and explain engagement in software visualization. The expected output of this study was a list of the factors that have a positive impact on learner engagement in SV tools.Â Â